Empathy and citizen’s social-political attitude: age as a moderator - Liu, Yingjuan; Lu, Lin; Kaviani, Hossein; Bao, Qingxiang; Li, Junjie (Frontiers in Psychology, 2026)
IntroductionBuilding upon prior research linking empathy to political attitudes, this study examines whether age moderates the relationship between empathy and democratic political attitudes—an area that remains underexplored.MethodsThe sample comprised 400 Chinese university students (aged 18–25) and 333 older adults (aged 45–60). Participants completed validated measures assessing empathy and support for democracy, with analyses controlling for normative identity style and demographic factors.ResultsResults indicated that empathy was positively associated with democratic attitudes. Importantly, after controlling for covariates, this positive association remained statistically significant only in the younger cohort, but not among older adults.DiscussionThese findings highlight age-dependent mechanisms in political psychology, suggesting that the drivers of political attitudes differ across generations. The results offer empirical insights for developing political leadership frameworks sensitive to China’s unique sociopolitical environment.